2019
DOI: 10.1111/aogs.13725
|View full text |Cite
|
Sign up to set email alerts
|

Grandmultiparity, maternal age, and the risk for uterine rupture—A multicenter cohort study

Abstract: Introduction:Uterine rupture is a critical complication causing fetal and maternal morbidity and mortality. Data are conflicting regarding whether grandmultiparity (parity ≥ 6) is a risk factor. This multicenter cohort study aimed to determine whether grandmultiparity (parity ≥ 6) poses a risk for uterine rupture in women with no previous cesarean delivery. Material and methods:A multicenter retrospective study of deliveries that occurred between the years 2003 and 2015 in three tertiary medical centers. Deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…This study also revealed women who were para one were 88% less likely to have uterine rupture than women with multiparity. This finding is supported by different prior studies in different countries in Ethiopia 42 , Norway 8 , 69 , Senegal and Mali 56 , Uganda 51 , and Israel 70 . It might be attributed to the fact as increasing parity increases the elasticity and strength of the uterine muscle (Myometrium) decreases 38 , 71 .…”
Section: Discussionsupporting
confidence: 81%
“…This study also revealed women who were para one were 88% less likely to have uterine rupture than women with multiparity. This finding is supported by different prior studies in different countries in Ethiopia 42 , Norway 8 , 69 , Senegal and Mali 56 , Uganda 51 , and Israel 70 . It might be attributed to the fact as increasing parity increases the elasticity and strength of the uterine muscle (Myometrium) decreases 38 , 71 .…”
Section: Discussionsupporting
confidence: 81%
“…The WHO defined low parity (LP) women as those having less than five pregnancies (live or stillborn) with gestation periods of ≥20 weeks, and high parity (HP) women were defined as those having five or more pregnancies (live or stillborn) with gestation periods of ≥20 weeks [ 1 , 2 ]. Hence, the term LP includes primipara and multipara, while HP includes grandmultipara and great grandmultipara.…”
Section: Introductionmentioning
confidence: 99%
“…HP decreased in the Western part of world and its prevalence is around 4%, but in the Eastern part of the world, HP is around 10.2%, which is more than double [ 2 ]. HP is associated with risks of maternal and fetal complications, such as gestational diabetes mellitus (GDM), hypertensive disorders, maternal anemia, preterm labor, miscarriage, postpartum hemorrhage, congenital malformations, macrosomia, and perinatal and preterm mortality [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous rupture has been reported after uterine artery embolization or in unscarred uterus as well. Maternal age has also been associated with increased risk(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%